PARTISIPASI MASYARAKAT DALAM MENGATASI BANJIR ROB DI KOTA SEMARANG (STUDI KASUS : KELURAHAN PANGGUNG LOR KOTA SEMARANG) - Marlitha Nusa Prashayu; Sulistyowati .; Priyatno Harsasto; Edi Santosa (Journal of Politic and Government Studies, 2018)
AbstractThe coastal flood in Semarang City needs to get special attention from the city government. In Semarang City this problem has occurred long enough and getting worse. Semarang city especially in the north side or often called Semarang Bottom extremely vulnerable to high potential. The resultof the occurrence of coastal flood is certainly quite disruptive social activities, such as the access road, the center of trade and service cause the economy of the community was disrupted. This problems needs complex handling. The role of the Governments and participation is the key to solve the coastal flood.The methods used in this studi using descriptive qualitative research design, by doing data collection techniques such as interview, observation, and documentation. The informant in this research are The Head of The Panggung Lor Village, The Head Of the Paguyuban Penannggulangan dan Pengendalian Air Pasang Panggung Lor (P5L), and the community of the Panggung Lor Village.The results of this research show that the participation of the community Stage keluarahan Lor has managed to overcome the problem of flooding in the village of rob. The participation of the community in the form of participation of the Lor Village Stage money, property, effort, time, and thought.One of the recommendations that can be given to addressing that problem is, the Government should focus more against coastal flood problem considering that this issue already happened long enough, in tackling the coastal flood problem the Government can also invite the public to participate.Keywords: Social Engagement, Coastal Flood, Rob, P5L